2008
DOI: 10.48550/arxiv.0810.5643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pseudo-Hermitian Representation of Quantum Mechanics

Ali Mostafazadeh

Abstract: A diagonalizable non-Hermitian Hamiltonian having a real spectrum may be used to define a unitary quantum system, if one modifies the inner product of the Hilbert space properly. We give a comprehensive and essentially self-contained review of the basic ideas and techniques responsible for the recent developments in this subject. We provide a critical assessment of the role of the geometry of the Hilbert space in conventional quantum mechanics to reveal the basic physical principle motivating our study. We the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
196
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(199 citation statements)
references
References 163 publications
(367 reference statements)
2
196
0
1
Order By: Relevance
“…[27][28][29], leading to the average of an observable O(t) given by O(t) ≡ tr [ρ N (t)O(t = 0)]. On the other hand, the Lindblad equation with η-pseudo-Hermitian Hamiltonians [30], for which ηHη −1 = H † with η being a Hermitian metric operator in the Hilbert space h, has been derived in Refs. [31,32] for the generalized density matrix ρ G (t) ≡ ρ(t)η, viz.,…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29], leading to the average of an observable O(t) given by O(t) ≡ tr [ρ N (t)O(t = 0)]. On the other hand, the Lindblad equation with η-pseudo-Hermitian Hamiltonians [30], for which ηHη −1 = H † with η being a Hermitian metric operator in the Hilbert space h, has been derived in Refs. [31,32] for the generalized density matrix ρ G (t) ≡ ρ(t)η, viz.,…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that, albeit relevant, the role played by the PT symmetry and the C operator is not a fundamental one. Indeed, it can be seen from PHQM that η = CPT is just an example of a positive-definite metric operator [21]. In fact, the existence of a preferred metric, and its physical meaning, is an open issue in the PHQM.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the existence of a preferred metric, and its physical meaning, is an open issue in the PHQM. There are several contexts where pseudo-hermitian operators appear [21]. In special, recent treatments of topological aspects of non-hermitian systems use the framework of PHQM [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few years ago [2] it was noticed that this condition coincided with the requirement that the continuous spectrum of the corresponding optical potential includes certain points known to mathematicians as spectral singularities [3,4]. Spectral singularities entered into physics literature as mathematical obstructions [5,6,7] to a Hermitization procedure developed to construct unitary quantum systems using certain non-Hermitian Hamiltonian operators [8,9]. Spectral singularities turn out to have an interesting physical meaning [10]; they correspond to a special class of scattering states with a real and positive energy that behave exactly like resonances.…”
Section: Introductionmentioning
confidence: 99%